Application of liquid biofertilizer (green technology) to enhance impact of chemical fertilizers on yield of hydroponically grown herbs and vegetables - Surimin, Adilah; Shamsuddin, Zulkifli (Program Pemindahan Ilmu - Kementerian Pendidikan Malaysia, 2014)
Hydroponic system has received positive and encouraging response by urban dweller and rural resident alike due to limited land resource and escalating food, herbs and vegetable. However, the chemical fertilizers be used are costly and can alleviate the possible environmental hazard. Under the Knowledge Transfer Programme (KTP), the green technology of environmentally friendly liquid biofertilizer (Becto10®) was used. It provided ‘free’ nitrogen by biochemically fixing gaseous nitrogen. Knowledge transfer program started since receiving the grant September 2012 and will end in September 2014. This technology was applied to vegetable herbs, viz pegaga (Centella asiatica) at Soil Microbiology Laboratory and Faculty Agriculture Glass House, UPM. This portable technology will be transfer to Kazz Hydroponics Sdn. Bhd in Kompleks Industri Bersepadu Duyong, Melaka. Expected results of the program are produces high quantity and quality of vegetable herbs at lower cost and formation of simple, innovative and sustainable production of organic herbs.